Low Release Study of Cefotaxime by Functionalized Mesoporous Silica Nanomaterials - Dan Eduard Mihaiescu; Daniela Istrati; Alina Moroșan; Maria Stanca; Bogdan Purcăreanu; Rodica Cristescu; Bogdan Ștefan Vasile; Roxana Doina Trușca (Gels, 2022)
As a third-generation β-lactam antibiotic, cefotaxime shows a broad-spectrum with Gram-positive and Gram-negative bacteria activity and is included in WHO’s essential drug list. In order to obtain new materials with sustained release properties, the present research focuses on the study of cefotaxime absorption and desorption from different functionalized mesoporous silica supports. The MCM-41-type nanostructured mesoporous silica support was synthesized by sol–gel technique using a tetraethyl orthosilicate (TEOS) route and cetyltrimethylammonium bromide (CTAB) as a surfactant, at room temperature and normal pressure. The obtained mesoporous material (MCM-41 class) was characterized through nuclear magnetic resonance (NMR), scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HR-TEM), N2 absorption–desorption (BET) and Fourier transform infrared spectroscopy (FT-IR), proving a good micro-structured homogeneity (SEM images), a high surface area (BET, 1029 m2/g) correlated with high silanolic activity (Q3/Q4 peak ratio from 29Si MAS-NMR), and an expected uniform hexagonal structure (2–3 nm, HRTEM). In order to non-destructively link the antibiotic compound on the solid phase, MCM-41 was further functionalized in two steps: with aminopropyl trimethoxysilane (APTMS) and glutaraldehyde (GA). Three cefotaxime-loaded materials were comparatively studied for low release capacity: the reference material with adsorbed cefotaxime on MCM-41, MCM-41/APS (aminopropyl silyl surface functionalization) adsorbed cefotaxime material, and APTMS–GA bounded MCM-41—cefotaxime material. The slow-release profiles were obtained by using an on-flow modified HPLC system. A significant improved release capacity was identified in the case of MCM-41/APS/GA—cefotaxime due to the covalent surface grafting of the biological active compound, recommending this class of materials as an effective carrier of bioactive compounds in wound dressing, anti-biofilm coatings, advanced drugs, and other related applications.